La historia del ciego mártir Damián de Yamaguchi en los manuscritos de Gil de la Mata (Siglo XVI) - Giuseppe Marino (Janus: Estudios sobre el Siglo de Oro)
This article aims to provide two unpublished manuscripts by Jesuit Gil de la Mata, dating back to the first contact of Christianity in Japan from century XVI, and includes historical contributions about the Martyr Damian Yamaguchi. These documents, also translated into Portuguese by Luís Fróis in his History of Japam, narrate interesting anecdotes about the life of this character in his murdered years before. His ability to preach and to convert his countrymen, including his singular craft of unknown exorcist came to impact many authors who narrated some events of this unusual man. This essay offers another vision of Brother Damian, blind catechist for a long period, who had to replace the Jesuits expelled upon precept daimyo Hideyoshi.